Organic-inorganic hybrid halide perovskites impregnated with Group 1 and 15 elements for solar cell application. (September 2020) - Dey, Pritam; Singh, Harish; Gupta, Rahul K.; Goswami, Debabrata; Maiti, Tanmoy
Abstract: In this report, we explored the substitution of triple cations at B-site of ABX 3 perovskite architecture in inorganic-organic hybrid perovskite materials in order to improve its stability over moisture and heat, which is considered as the paramount obstacles for commercialization of perovskite solar cell. In the current investigation we synthesized two novel perovskite materials, Methylammonium potassium bismuth lead iodide [ CH 3 NH 3 K 0.25 Bi 0.25 Pb 0.5 I 3 ] (MKBPI) and Methylammonium sodium bismuth lead iodide [ CH 3 NH 3 Na 0.25 Bi 0.25 Pb 0.5 I 3 ] (MNBPI). XRD studies confirmed hexagonal crystal structure with P63 /mmc space group for both the perovskites. Antisolvent treatment improved the surface coverage and morphology of the thin films, observed in FESEM. UV–Vis spectra demonstrated high absorption coefficient. Band gap was estimated as 2.09 eV for MKBPI. Fluorescence decay kinetics study revealed charge carrier lifetime on the order of nano second. DSC and TGA measurements confirmed thermal stability of these perovskites up to 280 °C. Further, we carried out detailed degradation study using XRD and UV–Vis spectroscopy of these perovskite thin films kept at ambient atmosphere for two weeks. Remarkably thin films of these perovskites exhibited good absorption even after 14 days. Graphical abstract: Image 1 Highlights: Synthesized thin films of halide perovskites with triple cations at B-site. Exhibited good absorption coefficient, good charge carrier lifetime (17–32 ns). Obtained band gap of 1.86 eV and 1.14 eV for MKBPI and MNBPI, respectively. Degradation studies carried out by XRD, UV–Vis and DSC-TGA over 15 days. Multiple cations in B-site produced stable organometallic halide photovoltaics.